Review of the genus Cnemaspis Strauch, 1887 (Sauria: Gekkonidae) in Sri Lanka with the description of five new species - Wickramasinghe, L. J.mendis; Munindradasa, D. A.i. (Zootaxa, 2007)
Five new species of geckos are described from Sri Lanka by morphological comparison and morphometric analysis leading to review the genus Cnemaspis in the country. The type series of these species were identified from following localities: C. alwisi and C. kumarasinghei from the intermediate zone, C. retigalensis from the dry zone, C. molligodai from the lowland wet zone and C. samanalensis from the mountain region of the wet zone in the country. The high degree of endemicity (90%) shown by Cnemaspis in Sri Lanka could be attributed to geographical isolation. In addition, the taxonomic issue of C. jerdonii scalpensis is discussed and the species C. scalpensis is errected.